x+15-26+6=x

Simple and best practice solution for x+15-26+6=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+15-26+6=x equation:


Simplifying
x + 15 + -26 + 6 = x

Reorder the terms:
15 + -26 + 6 + x = x

Combine like terms: 15 + -26 = -11
-11 + 6 + x = x

Combine like terms: -11 + 6 = -5
-5 + x = x

Add '-1x' to each side of the equation.
-5 + x + -1x = x + -1x

Combine like terms: x + -1x = 0
-5 + 0 = x + -1x
-5 = x + -1x

Combine like terms: x + -1x = 0
-5 = 0

Solving
-5 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 24=12b+8c | | X-2x+2+3x= | | (4y+1)(5y+7)= | | 2x=32 | | -6(x-6)=36 | | senx+1=cosx | | -5(x-3)+2x= | | 3/4=b/32 | | 5x+-3=2(3+x) | | 4/8+2= | | 4(a-6)=4a-10 | | f(-27.018)=31.572x-17.741 | | 4a-(a-5)=23 | | f(6.2)=31.572x-17.741 | | 6z+24=6(2+4) | | -b*-1=-3m+1 | | 8-7x-5-7x=5 | | (2x^2-2x-4)+(-4x^2+5x-1)= | | 5(x-2)-4(3x+3)=4x-11 | | b-15=24 | | -3(x+3)=6x+63 | | 0.02+0.7=0.8 | | (2x^2-4x-6)+(-5x^2-6x-3)= | | 81=1.25+3.25 | | 7x+5x=550 | | 3x-50=2 | | b/4-5=6 | | 3x-3=50 | | 3tan^2x+10tanx-25=0 | | (2b-12)+b=33 | | 2l+o=-4 | | 9c-1=c-25 |

Equations solver categories